Anti-inflammatory protective effect of cannabidiol extracted from Cannabis sativa L. (hemp) against SARS-CoV-2 infection: A review of the literature (Revista Médica de Trujillo, 2024)
Cannabidiol (CBD) is a non-psychotropic phytocannabinoid derived from cannabidiolic acid and has anti-inflammatory, analgesic, antineoplastic, and chemopreventive properties that even enhance the immune system thanks to the human endocannabinoid system. It is due to these characteristics that studies have been carried out to test its effectiveness as a treatment option against COVID-19, which meets the global medical goal of combating this disease since it became a pandemic in early 2020. CBD has been reported to have antiviral activity against the coronavirus, in addition to reducing the expression of the ACE-2 enzyme and the levels of proinflammatory cytokines, which results in structural and functional improvements of the tissues infected by SARS-CoV-2.
Keywords: Cannabidiol; COVID-19; Immune System